Revision of the genus Aulacophora from Taiwan (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng; Beenen, Ron (Zootaxa, 2015)
Ten species of the genus Aulacophora Chevrolat, 1836 are reported for Taiwan. Specimens of A. opacipennis Chûjô, 1962 collected from Southeast Asia were misidentified by Kimoto (1989) and should be identified as A. apicipes Jacoby, 1896. Color photos of habitus and drawings of male and female genitalia from eleven species (including A. apicipes) are presented. The following synonymies are proposed: Aulacophora analis (Weber, 1801) = Galeruca quadraria Olivier, 1808 (syn nov.); A. indica (Gmelin, 1790) = Rhaphidopalpa pubescens Allard, 1888 (syn. nov.); A. apicipes Jacoby, 1896 = A. nigripalpis Chen and Kung, 1959 (syn nov.). Lectotypes are designated for Crioceris abdominalis Fabricius, 1781, C. testacea Fabricius, 1787, Galleruca bicolor Weber, 1801, Galeruca quadraria Olivier, 1808, Aulacophora semiopaca Jacoby, 1886, A. frontalis Baly, 1888, A. lewisii Baly, 1886, A. intermedia Jacoby, 1892, A. semifusca Jacoby, 1892, A. dohrni Jacoby, 1899, A. almora Maulik, 1936, A. apicipes Jacoby, 1896, A. tenuicincta Jacoby, 1897, Rhaphidopalpa pubescens Allard, 1888, R. bengalensis Weise, 1892, R. ceramensis Weise, 1892, R. chinensis Weise, 1892, and Orthaulaca (Ceratia) cattigarensis Weise, 1892. A key to the Taiwanese species is provided.